(untitled) (Research, Society and Development, 2021)
Objective: The objective of this case report was to demonstrate color matching between incisors and canines through tooth whitening Methodology: Based on the patient’s permission through the Informed Consent Form (FICF) to share her image for the proper purpose, the present This study deals with a clinical case report of descriptive analytical nature (Pereira et al., 2018), Clinical case report: Patient GMC, male, 26 years old, feoderma, attended the Fametro University Faculty, with the main complaint “ My teeth are yellow. As I work with the public, the smile bothers me a little” the intraoral exam was performed and a yellowish hue was observed in all elements. However, some questions were asked related to the aesthetics of her smile, which she reported is not satisfied, feeling like this with low self-esteem. Dental whitening using the in-office technique was given as an option for the treatment. Final considerations: The in-office bleaching technique using 35% hydrogen peroxide as a bleaching agent proved to be effective and color change in canines may require a greater number of sessions to obtain a color pattern that is harmonious with incisors.